The PD1:PD-L1/2 Pathway from Discovery to Clinical Implementation - Bardhan, Kankana; Anagnostou, Theodora; Boussiotis, Vassiliki A. (Frontiers in Immunology, 2016)
The immune system has the difficult challenge of discerning and defending against a diversity of microbial pathogens, while simultaneously avoiding self-reactivity. T lymphocytes function as effectors and regulators of the immune system. While central tolerance mechanism results in deletion of the majority of self-reactive T lymphocytes during thymic selection, a fraction of self reactive lymphocytes escapes to the periphery and retains the potential to inflict destructive autoimmune pathology. The immune system evolved various mechanisms to restrain such auto-reactive T cells and maintain peripheral tolerance, including T cell anergy, deletion, and suppression by regulatory T cells (TRegs). These effects are regulated by a complex network of stimulatory and inhibitory receptors expressed on T cells and their ligands, which deliver cell-to-cell signals that dictate the outcome of T cell encountering with cognate antigens. Among the inhibitory immune mediators, the pathway consisting of the programmed cell death 1 (PD-1) receptor (CD279) and its ligands PD-L1 (B7-H1, CD274) and PD-L2 (B7-DC; CD273) plays a vital role in the induction and maintenance of peripheral tolerance and for the maintenance of T cell homeostasis. In contrast to its beneficial role in self-tolerance, the PD-1: PD-L1/L2 pathway mediates potent inhibitory signals that prevent the expansion and function of T effector cells and have detrimental effects on antiviral and antitumor immunity. Therapeutic targeting of this pathway has resulted in successful enhancement of T cell immunity against viral pathogens and tumors. Here, we will provide a brief overview on the properties of the components of the PD-1 pathway, the signaling events that are regulated by PD-1 triggering, and their consequences on the function of T effector cells.